2023
DOI: 10.1093/femsre/fuad028
|View full text |Cite
|
Sign up to set email alerts
|

Have genetic targets for faecal pollution diagnostics and source tracking revolutionized water quality analysis yet?

Abstract: The impacts on faecal pollution analysis using nucleic acid-based methods, such as PCR and sequencing, in health-related water quality research were assessed by rigorous literature analysis. A wide range of application areas and study designs has been identified since the first application more than 30 years ago (>1,100 publications). Given the consistency of methods and assessment types, we suggest defining this emerging part of science as a new discipline: genetic faecal pollution diagnostics (GFPD) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 270 publications
(344 reference statements)
1
1
0
Order By: Relevance
“…The collective findings underscore the significance of MST in pinpointing the specific hosts responsible for potential impacts on river water quality. This importance of MST has also been emphasized in previous studies [44][45][46][47].…”
Section: Plos Watersupporting
confidence: 55%
“…The collective findings underscore the significance of MST in pinpointing the specific hosts responsible for potential impacts on river water quality. This importance of MST has also been emphasized in previous studies [44][45][46][47].…”
Section: Plos Watersupporting
confidence: 55%
“…Box 4. Use of Microbial Source Tracking Genetic Targets for Water Quality [13] The impact on faecal pollution analysis in health-related water quality research by nucleic acid-based methods, such as PCR analysis and sequencing, was assessed by rigorous literature analysis. A wide range of application areas and study designs was identified, since the first application more than 30 years ago (>1,000 publications).…”
Section: Use Of Innovative Molecular Methodsmentioning
confidence: 99%
“…This fact can be partly explained by the association of Bacteroides with the diet of urban populations [ 14 ]. Due to the high prevalence of crAssphages in the human intestine, it is currently proposed to monitor their levels in treated wastewater to detect contamination with human feces [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%